The Pharisees in Mark : comparing their social-historic role and their narrative function - Magda, Ksenija (Array, 2019)
The main purpose of this paper is to compare the facts about the Pharisees that we learn from extra-biblical sources against the facts we learn from the narrative in Mk. 1:21-3:35, with the purpose of setting a historical foundation for Mark’s account. In the first section we show the available historical accounts and we conclude it to be ambivalent, while in the second section we portray the developing conflict between Jesus and the Pharisees, which in turn sheds light on historical facts in line with the conclusion that Mark’s description of the Pharisees is historically plausible, because of this Mark’s Gospel can be used for its contribution to the historical discussion about the Pharisees. The paper is divided into two sections. The first, historical, section deals with the attempt to reconstruct the relationship between Jesus and the Pharisees based on historical data, and the second, exegetic section, uses narrative criticism to develop the history and the kerygma.